Relationship Of Mother Factors With Low Birth Weight (LBW) Infants Which Are Treated In DR.M. Djamil Central Public Hospital Padang - Novela Delfita; Desmiwarti Desmiwarti; Meilinda Agus (Journal of Midwifery, 2017)
Low Birth Weight (LBW) is an infant born with a weight less than 2500 grams. LBW is one of the causes of the high rate of morbidity and infant mortality, and the low quality of human resources. The occurrence of LBW is related to the condition of the mother during pregnancy. This study was aimed to determine the factors associated with the occurrence of LBW.This was a qualitative study with case control study design. The subject of the study was the mother of the LBW infant being treated at Dr. M. DjamilCentral Public Hospital Padang as many as 36 respondents (cases), and mothers of infants who were treated with other diseases as much as 36 respondents (control) from July to mid September 2017 taken by Consecutive Sampling. Data collection was done by filling out questionnaires, observation of medical record data, and measurement of upper arm circumference. Data were analyzed univariate by using frequency distribution and bivariate using chi square test with the degree of meaning 5% (p-value=<0,05).The result of the analysis showed that there was a correlation between maternal age at risk with LBW infants, there was a relationship of poor mother's nutritional status with LBW infants, there was a parity relationship of primiparous mother with LBW infant, there was a relationship of mother who suffered one or more medical illness with LBW infant, there was no relationship of gestational distance to LBW infants, and there was a tendency for the relationship between gemelli gestation and LBW infants.Maternal age, maternal nutritional status, parity, and maternal medical illness are associated with LBW infants treated in Dr. M. Djamil Padang. Regular and periodic monitoring and examination of pregnancy is important to prevent the baby from being born with LBW.